High School Dropout: The Students’ Perspective - Salvà-Mut, Francesca; Universidad de las Islas Baleares (Editorial Pontificia Universidad Javeriana, 2014)
This study addresses the problem of high school dropout in Spain. It aims to gain a more profound understanding of the reasons and processes that lead to students leaving school, based on the point of view of the teenagers themselves. A qualitative methodology and a biographical approach were chosen. The results reveal the multiple factors that play a role, and the fact that high school dropout should be seen as a process. They also show the roles of the different actors, the influence of a group of equals, and the challenges of educational institutions and families to fulfill their educative duties.